IT INDUSTRY IN BOTSWANA: CHALLENGES AND OPPORTUNITIES - Priti, Jain (Malaysian Journal of Library and Information Science, 2002)
This paper discusses the IT industry in Botswana in the context of five major findings of recently conducted surver. Looking at the challenges and opportunities facing the industry, the paper provides proposals on what needs to be done by all stakeholders including the government, the private sector and individual institutions to mitigate the challenges facing the industry and build on the opportunities available to enhance IT growth in Botswana.